Teaching Macro Excel on Pre-service Mathematics Teachers: Analysis Error in Solving the Syntax Manually - Wulandari, Nourma Pramestie; Wahiduddin, Faishal; Lu'luilmaknun, Ulfa; Maulyda, Mohammad Archi; Apsari, Ratih Ayu (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The aim of this study is to describe errors output when pre-service mathematics teachers were writing output of the syntax that given in macro excel manually. This research is a qualitative descriptive research with 101 participants from 2nd year pre-service mathematics teachers from one of state university at Nusa Tenggara Barat, Indonesia. Instrument used consists of one syntax that has 8 outputs when it is run and that will be analysed using Newman’s procedures. The eight outputs come from 3 types of output, namely text, numbers, and count. The result showed that the average percentage of syntax output writing errors was 87.13%. It also indicated to reading errors of 48.51%, comprehension errors of 18.81%, transformation errors of 83.17%, process skill errors of 20.79%, and encoding errors of 87.13%. Based on the result, errors occur when participants incorrectly write output and wrong in writing the result of the count. In addition, factors that caused these errors are 1) participants were not trained in providing information that was in the problem, 2) participants did not read the instructions in the problem correctly, and 3) participants did not pay attention to the suitability of syntax and output as was learned before. This research can be a reference for lecturers to develop learning about programming languages that can make students understand the use of syntax with the emphasis on manual syntax learning which will make their logic easier when applyng the syntax on a computer.